Evaluation of Socioeconomic and Occupational Barriers to Breastfeeding: A Comparative Study Among Weaving Mothers - Marni Siregar; Hetty Panggabean (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
In Indonesia, stunting continues to affect many children, making breastfeeding practices a critical focus of early prevention.  Mothers working in the informal sector, such as traditional weavers, often encounter occupational and socioeconomic barriers that may hinder optimal breastfeeding. This study aims to describe the sociodemographic characteristics of weaving mothers and compare the mean scores of Early Initiation of Breastfeeding (EIBF) implementation and knowledge of exclusive breastfeeding between North Tapanuli and Samosir, North Sumatra. A cross-sectional study was conducted among 72 weaving mothers, with 36 respondents from Siatas Barita Health Center, (North Tapanuli) and 36 from Buhit Health Center (Samosir) selected through purposive sampling. Data were collected using a structured questionnaire and analyzed descriptively through frequency distributions, percentages, and mean scores. Most respondents were aged 26–35 years and had completed senior high school. The mean EIBF score was 3.19 in North Tapanuli and 2.89 in Samosir, both classified as high. The mean score for exclusive breastfeeding knowledge was 3.25 in North Tapanuli (very high) and 2.79 in Samosir (high). These findings suggest that weaving mothers in North Tapanuli had higher EIBF implementation and higher knowledge of exclusive breastfeeding knowledge compared to  those in Samosir. Region-specific breastfeeding education and community-based support are recommended, particularly in Samosir, to strengthen maternal knowledge and promote optimal breastfeeding practices. Keywords: Breastfeeding, Occupational Barriers, Weaving Mothers, Comparative Study.